Risk factors and outcomes of non-albicans candida bloodstream infection in patients with candidemia at siriraj hospital— thailand’s largest national tertiary referral hospital - Chaiyapong Ngamchokwathana (2022)
This study aimed to investigate the risk factors for and the outcomes of patients with candidemia caused by non-albicans Candida. Candidemia patients treated at Siriraj Hospital (Bangkok, Thailand) during January 2016 to December 2017 were enrolled. A total of 156 patients (mean age: 65 years, 56.4% male) were included. The most prevalent underlying conditions were diabetes (32.1%), chronic cardiac disease (28.2%), chronic kidney disease (26.9%), and hematologic malignancies (21.2%). Candida species isolated from patient blood were C. tropicalis (49.4%), C. albicans (28.8%), C. glabrata (16.7%), and C. parapsilosis (5.1%). Fluconazole resistance was significantly increased in C. tropicalis (37.8%). No independent risk factors were associated with patients with non-albicans Candida candidemia compared to those with C. albicans candidemia. There was no significant difference in mortality between patients with non-albicans Candida candidemia and patients with C. albicans candidemia (OR: 1.35, 95% CI: 0.64–2.85). When compared with C. albicans candidemia, multivariate analysis revealed chronic liver disease (OR: 11.39, 95% CI: 1.38–94.02), neutropenia (OR: 4.31, 95% CI: 1.34–13.87), and male gender (OR: 2.34, 95% CI: 1.04–5.29) to be independent risk factors for C. tropicalis candidemia. The observed high resistance of C. tropicalis to fluconazole indicates that fluconazole should not be used for empirical antifungal treatment in these patients.